Molecules : A Very Short Introduction - Ball, Philip, 1962- (Oxford, New York Oxford University Press, 2003)
The processes in a single living cell are akin to that of a city teeming with molecular inhabitants that move, communicate, cooperate, and compete. In this Very Short Introduction, Philip Ball explores the role of the molecule in and around us - how, for example, a single fertilized egg can grow into a multi-celled Mozart, what makes spider's silk insoluble in the morning dew, and how this molecular dynamism is being captured in the laboratory, promising to reinvent chemistry as the central creative science of the century.
Include Illustration, Notes and Index
Keywords: Molecules -- Chemistry